Scholarly Views on ‘Dialogue of Life’ as a Facilitator for Christian-Muslim Intermarriages in Ghana - Kuyateh, Mustapha Abdullah; Ibrahim, Alhaji Iddrisu Hussein (Borneo International Journal of Islamic Studies, 2024)
The term ‘dialogue of life’ is usually used to display the phenomenon of living together of people of different religious persuasions, carrying out daily life interactions among themselves. Although coexistence of Ghanaians of multi-religious society had begun long before pre-independence when they frequently met and shared activities together, we fail to recognize that this kind of social interaction is part of the interreligious dialogue operating at the grass roots level. This is especially so when it comes to Christian-Muslim intermarriages. In Ghana, it is always a thorny issue among religious leaders when it comes to approving marriages between Muslims and Christians. Both religious groups are opposed to giving their approval and blessings to Christian-Muslim marriages. The crux of their opposition centre son differences in belief. Scholars appear to have failed to realize that this increasing occurrence of intermarriages within and across boundaries is an impact of globalization frequently overlooked.